Liquid phase styrene epoxidation catalyzed by rice husk ash silica derived mesoporous calcium silicate and calcite-type calcium carbonate catalyst - Iqbal, Anwar; Tan, Kok-Hou; Adam, Farook; Abu Bakar, Noor Hana Hanif; Ahmad, Mohammad Norazmi; Yusop, Muhammad Rahimi (Chiang Mai University, 2020)
A series of rice husk ash silica derived mesoporous calcium silicate, and calcium carbonate catalysts were synthesized via a direct one-pot synthesis technique by varying the calcium/CTAB molar ratio (0.25, 0.50, 0.75, and 1.00). The aragonite-type calcium carbonate crystalline phase was formed on the catalyst surface when the Ca/CTAB molar ratio was < 1.00, whereas calcite-type calcium carbonate was formed when the Ca/CTAB ratio=1.00. The catalyst with the highest calcium content (1.00CaMST) with calcite-type calcium species was found to be the most active in styrene epoxidation reaction using H2O2 oxidant at mild conditions (60 °C, 3 h). The conversion of styrene and styrene oxide selectivity was 66.9% and 79.2%, respectively. Octahedrally coordinated calcite active sites were identified as more accessible to H2O2 molecules than the nine-fold coordinated aragonite active sites. The product selectivity changed when the catalyst was reused due to the decomposition of carbonate surface active sites. The selectivity of benzaldehyde and phenylacetaldehyde increased when 1.00CaMST was used for the third and fourth cycles.